HUBUNGAN ANTARA PENYESUAIAN DIRI DAN KEBAHAGIAAN MAHASISWA TAHUN PERTAMA - Al Imania; Hartanti Hartanti; Darmawan Muttaqin (Perpustakaan Universitas Surabaya, 2018)
This study aims toobserve the relat ionship between self -adjustment and the fresehmen’ happiness. The population in this research is the freshmen ofSurabaya University in academic year of 2016 who come from outside Surabaya.This research uses an accidental sampling technique with the number of respondents 79 students.The research is a quantitative research with data collectionmethodology using instruments such as The Student Adaptation to College Questionnaire (SACQ) and happiness, supported by the demographic data such as sex, origin, nations, recent domicile, and faculty. The hypothesis uses parametric test and the result shows that there is a relationship between self-adjustment with happiness. Self-adjustment has a positive correlation and significance with happiness (r = 0,816, p≤0,05), and the most dominant of self-adjustment is academic adjustment aspect. From the crosstab analysis can be found th